Implementation of Customer Satisfaction Levels Towards Employee Services at Alkahfi Optikal Store - Maidalena, Maidalena; Nurhasanah, Alfa; Rahmah, Mutiara (Universitas Islam Negeri Sumatera Utara, 2023)
This study explores the application of customer satisfaction level related to employee service at Alkahfi Optikal Store through literature review method. In today’s competitive business environment, achieving high customer satisfaction is crucial to maintain customer loyalty and improve business performance. This study uses situational approach and focus group discussion as part of community service program to assess how employee performance affects customer satisfaction at Alkahfi Optikal Store. This study uses focus group discussion to gather insights from various stakeholders and analyze employee performance and customer feedback. Data collected through these discussions provide comprehensive understanding of the current state of employee service and its impact on customer satisfaction. Findings show that 48% of customers are satisfied with employee service at Alkahfi Optikal Store, while 5% expressed dissatisfaction due to communication misunderstanding. This shows that most customers rate service quality positively but highlight areas for improvement. This study emphasizes the important role of employee motivation in improving service quality and customer satisfaction. Motivated employees are more likely to provide exceptional service, which in turn increases customer satisfaction and loyalty.